Organic farming brand identity : meeting trends, building trust - Nikodemska-Wolowik, Anna Maria (Pecvnia : Revista de la Facultad de Ciencias Económicas y Empresariales, Universidad de León, 2009)
The Organic Farming (OF) concept plays a significant role in contemporary market competition in European and other economies. This issue is the main target of the paper. The OF certification mark is dealt with as a specific brand and its meaning is presented from different points of view. The author puts special emphasis on creating customer benefits and trust due to the OF certification mark. The mark can become an effective tool of building strong relationship between supply and demand sides of the market. El concepto de Agricultura Ecológica (AE) tiene un papel importante en la competencia del mercado contemporáneo tanto en la economía europea como en la de otros países. Este aspecto es el objetivo principal de este artículo. La certificación de AE se considera como marca específica y su significado se presenta desde diferentes perspectivas. El autor centra su atención en la creación del beneficio del consumidor y confianza debido a la certificación de marca de AL Ésta puede convertirse en una herramienta efectiva para la creación de una estrecha relación entre la oferta y la demanda del mercado.